Exploring the Impact of Advertising Appeal on Consumer Brand Awareness and Purchase Decisions in the Ready-to-Drink Packaged Tea Market: A Case Study of Teh Pucuk Harum in Pekanbaru - Azmi, Fauzan; Samsir, Samsir; Widayatsari, Any; Siregar, Prima Andreas (West Science Interdisciplinary Studies, 2024)
This study investigated the influence of advertising appeal on the brand image of Teh Pucuk Harum in Pekanbaru. This study was conducted quantitatively, using causal and descriptive research designs. A survey was conducted by distributing questionnaires; then, the data or information obtained were processed by statistical methods using SEM PLS analysis. The results show that advertising appeal significantly influences a company’s brand image (TBI). The quality of the advertising message does not have a direct effect on TBI. Advertising appeals do not affect the purchasing decision-making process. Advertising creativity does not influence the purchasing decisions of a company, and the quality of advertising messages has no significant effect on purchasing decisions. It is hoped that the company can convince consumers that the appeal of the caterpillar/endorse-shaped advertisement in the Teh Pucuk Harum advertisement is trustworthy and honest in conveying the message of the product.